The extent to which students in the first grade in Jeddah, Saudi Arabia, were able to master critical thinking skills in mathematics - Al Zahrani, Khalid bin Saeed (Journal of Educational and Psychological Sciences, 2018)
The aim of this study is to determine the extent to which students in the first grade in the Kingdom of Saudi Arabia have achieved critical thinking skills in mathematics. The study used a descriptive approach. To achieve the objectives of the study, the researcher designed a test that measures the level of students in four skills of critical thinking skills: prioritization, sequence, interpretation, and conclusion. The study found that the average grade of the students in the first level of critical thinking skills in mathematics was 35.66. In relation to the results related to the skills separately, the arithmetic averages were as follows: priority setting: 43.83, below the mean, 35.83 and 32.83, Conclusion 30.0. All of which are estimated to have not reached the 50.00 level of tolerance. The study recommended the need to review the educational contents included in the mathematics book for the first grade intermediate, to include subjects and mathematical issues that develop critical thinking. And holding training courses for teachers and teachers to familiarize them with critical thinking, skills, application and positive dimensions of learning and education.
Keywords: curricula; mathematics; first-grade intermediate students; critical thinking skills